Genetic Variability and Association Analysis for Yield and its Components in Alkaline and Inland Saline Stress in Rice (Oryza sativa L.) - Kandibanda, Sai Kylash; Gaddam, Shiva Prasad; Satturu, Vanisri; Saida Naik, D (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted at Agricultural Research Station, Kampasagar, Nalgonda, Telangana, India during the rabi season (December, 2020 to May, 2021) to identify suitable lines tolerant to alkalinity and inland salinity stress in rice. Analysis of variance evinced plenteous quantum of variability in all the 36 genotypes investigated. Phenotypic coefficients of variation were higher than genotypic coefficients demonstrating the effect of the prevalent stress environment. High estimates of genotypic coefficient of variation, phenotypic coefficient of variation, heritability, and genetic advance as percent mean was observed for the traits, seedling mortality, number of filled grains panicle-1 and sterility %. These findings suggested the preponderance of additive gene action for these characters. The remaining traits were mostly under the influence of non-additive gene effects as they recorded low to moderate estimates of genetic advance. Studies from association analysis showed that number of productive tillers hill-1 and number of filled grains panicle-1 had a positive significant correlation with yield whereas, seedling mortality and sterility % had a negative significant association with yield. Path analysis revealed that traits number of productive tillers hill-1, number of grains panicle-1 and 1000 grain weight had a positive direct effect on yield. Hence primacy should be given to the above-mentioned traits to develop alkalinity and inland saline tolerant and high yielding rice cultivars. Lines CT 118911, Sahel 177, M 202 and KPS 10654 were found to be promising entries and can be used tolerant parents in the breeding programme. Three principal components combined could explain 68.86% of the total variation.